PARTISIPASI POLITIK PEREMPUAN (STUDI KRITIS TERHADAP HAK KARIR POLITIK PEREMPUAN PERSPEKTIF WAḤBAH AZ-ZUḤAILĪ) - Fudhola', Muhammad Intiha'ul (Syariah: Journal of Fiqh Studies, 2023)
Long before talking about women in politics, the lives of women in various major civilizations of the world were very sad. Although on the other hand, accusations against the teachings of Islam that are considered to discriminate against women are endlessly thrown by orientalist groups. However, the facts show differently. Islam is the first religion to elevate the dignity of women. Based on these reasons, this study aims to reveal how Islam actually views political rights for women, especially Waḥbah az-Zuḥailī's perspective. This research uses a qualitative descriptive-analytic method. The main studies in this research are the books Qaḍāyā al-Fiqhi Wa al-Fikr al-Mu'āshir, al-Fiqh al-Islāmī wa Adillatuhu and Tafsīr Munīr. The results show that there are weaknesses in the arguments brought by Waḥbah az-Zuḥailī in ruling on women as the highest leader of the state. However, under certain conditions Waḥbah az-Zuḥailī still legalizes women's participation in politics and equalizes women's political position with men. There are two political activities that according to Waḥbah az-Zuḥailī are legal, among others: First, the right of women to choose leaders. Second, women's participation as members of parliament.